PENCARIAN CONTENT PORTAL WEB BERITA DENGAN TEKNIK SINDIKASI BERBASIS AJAX-SOAP WEB SERVICE - Suteja, Bernard Renaldy (Compiler, 2018)
Much of the latest information is spread through web news portals and has the difficulty of finding a desired content. It takes time to browse through many portals and identify the desired content. To track any updates from a web portal can be used Really Simple Syndication (RSS) technique. By using the technique of syndication it can be made a search engine that allows to bring the desired content from the number of news web portals. Implementation of AJAX-SOAP web service will make the resulting search engine responsive and have good interoperability.